2003
DOI: 10.1007/s10295-002-0001-5
|View full text |Cite
|
Sign up to set email alerts
|

Production of the secondary metabolites γ-aminobutyric acid and monacolin K by Monascus

Abstract: gamma-Aminobutyric acid (GABA), a hypotensive agent, and monacolin K, a cholesterol-lowering drug, can be produced by Monascus spp. Under optimal culture conditions, the products of fermentation using Monascus spp. may serve as a multi-functional dietary supplement and can prevent heart disease. In this study, Monascus purpureus CCRC 31615, the strain with the highest amount of monacolin K, was identified from 16 strains using solid fermentation. Its GABA productivity was particularly high. Addition of sodium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
186
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(194 citation statements)
references
References 22 publications
4
186
2
2
Order By: Relevance
“…Lovastatin production by SSF using Monscus. purpureus CCRC 31615 (19), M. purpureus NTU 601 (21), M. pilosus M12-69 (6), and M. ruber (22), are also reported in literature.…”
Section: Introductionmentioning
confidence: 87%
“…Lovastatin production by SSF using Monscus. purpureus CCRC 31615 (19), M. purpureus NTU 601 (21), M. pilosus M12-69 (6), and M. ruber (22), are also reported in literature.…”
Section: Introductionmentioning
confidence: 87%
“…(M. purpureus and M. ruber) has been employed in the preparation of Red-yeast rice (RYR), a traditional fermented food consumed in Asian countries as "red koji". Later, It was identified that lovastatin is a functional constituent of RYR [1,[13][14][15] . Monascus sp.…”
Section: Research Papermentioning
confidence: 99%
“…Monascus sp. was also exploited for various metabolites, viz., γ-aminobutyric acid, pigments, lipids, and structural analogues of lovastatin (pravastatin, compactin, monacolin J) [13,[16][17][18][19] . Endo [20] has first reported the production of lovastatin from Monascus sp.…”
Section: Research Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore these four medium parameters were chosen for further optimization by response surface methodology (3,19,20). The various levels of nutrients are summarized in Table 4.…”
Section: Screening Of Nutrient Parametersmentioning
confidence: 99%